Blackout / 2. - Black, Peter Jay (Urban Outlaws, 2015)
"The world's most destructive computer virus has been unleashed, and it's up to the Urban Outlaws--five tough kids dedicated to bringing justice to their city--to destroy it"--Provided by publisher.